Metadiscurso multimodal: análise dos esclarecedores das definições e exemplos de um dicionário de inglês - Ribeiro, Lorena Américo (2022)
In this paper, we examine multimodal resources that perform the metadiscursive function of clarifying the content of definitions and examples in the entries of the Collins COBUILD Illustrated Basic Dictionary of American English (2010). The study is based on Kress and van Leeuwen (2006), regarding the multimodal configuration of texts, on Hyland (1998, 2000, 2007, 2017), concerning the concept of metadiscourse, and on Kumpf (2000), Pontes (2010), Pontes and Fechine (2011, 2012), Fechine (2013), Rocha (2016), and Ribeiro and Pontes (2018), who discuss multimodal metadiscourse. We carried out an overview of the various elements that clarify the content of the definitions and examples in the dictionary and observed that, in general, the content is clarified either through verbal text or images. For this reason, we classified such elements as verbal and visual glosses. Then, we selected and analyzed representative samples of each type of gloss. We concluded that verbal and visual resources rework and even expand the text of definitions and examples in order to facilitate their understanding by a user who has limited knowledge of the English language.